Inhibitory mechanisms on dry anaerobic digestion: Ammonia, hydrogen and propionic acid relationship - Rocamora, Ildefonso; Wagland, Stuart T.; Hassard, Francis; Villa, Raffaella; Peces, Miriam; Simpson, Edmon W.; Fernández, Oliver; Bajón Fernández, Yadira (Elsevier, 2023)
Inhibitory pathways in dry anaerobic digestion are still understudied and current knowledge on wet processes cannot be easily transferred. This study forced instability in pilot-scale digesters by operating at short retention times (40 and 33 days) in order to understand inhibition pathways over long term operation (145 days). The first sign of inhibition at elevated total ammonia concentrations (8 g/l) was a headspace hydrogen level over the thermodynamic limit for propionic degradation, causing propionic accumulation. The combined inhibitory effect of propionic and ammonia accumulation resulted in further increased hydrogen partial pressures and n-butyric accumulation. The relative abundance of Methanosarcina increased while that of Methanoculleus decreased as digestion deteriorated. It was hypothesized that high ammonia, total solids and organic loading rate inhibited syntrophic acetate oxidisers, increasing their doubling time and resulting in its wash out, which in turn inhibited hydrogenotrophic methanogenesis and shifted the predominant methanogenic pathway towards acetoclastic methanogenesis at free ammonia over 1.5 g/l. C/N increases to 25 and 29 reduced inhibitors accumulation but did not avoid inhibition or the washout of syntrophic acetate oxidising bacteria.
Keywords: Propionic accumulation; Syntrophic acetogenic oxidation; Butyric accumulation; Methanoculleus; High solids digestion; Hydrogen inhibition